2018
DOI: 10.1108/inmr-05-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Framework for continuous agile technology roadmap updating

Abstract: Purpose Roadmapping has been used as an approach to support market, product and technology-integrated planning, resulting in a document commonly known as a roadmap. Despite the gains made in relation to the technique, recent studies indicate that most users leave or have difficulties in sustaining the process (i.e. maintaining the updated roadmaps). This paper aims to present a framework for continuous roadmap updating that incorporates principles from agile management fields. Design/methodology/approach The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The fourth factor, methods associated with roadmapping, was approached by Carlos et al (2018), as shown in 2.2. The three digital startups made the roadmapping integration to other methods.…”
Section: Analysis Of the Questionnaire Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fourth factor, methods associated with roadmapping, was approached by Carlos et al (2018), as shown in 2.2. The three digital startups made the roadmapping integration to other methods.…”
Section: Analysis Of the Questionnaire Resultsmentioning
confidence: 99%
“…Several roadmapping case studies have shown applications beyond traditional uses, as described by Souza (2018), such as its use with agile management methodology (SCRUM). Carlos et al (2018) have successfully proposed a continuous roadmapping update approach based on agile principles. Roadmapping, therefore, may be integrated into daily business process tasks to yield continuity in the method of an organization.…”
Section: Roadmapping In Agile Environmentsmentioning
confidence: 99%
See 3 more Smart Citations